Molecular docking of Cellobiose and Cellotetraose into an Endoglucanase from Fusarium oxysporum - Ibrahim Ali , Noorbatcha; Ahmad, Abdul Aziz; Hamzah, Mohd. Salleh (2013)
Endoglucanase is one of the three enzymes required to synergistically hydrolyze cellulose to sugar monomers which can be fermented into ethanol. Hence efforts to improve the efficiency of this enzyme, using experimental and computational approaches have been continuing vigorously. We have cloned an endoglucanase, FOegI, which is same as the well characterized endoglucanase I from Fusarium oxysporum (PDB ID: 3OVW), except for two mutations. As an attempt to improve the substrate binding characteristics of FOegI, we have carried computational molecular docking studies to understand the interactions in the active site regions and to suggest mutations to improve the binding characteristics. The docking of ligands into active site was carried out using Lamarkian genetic algorithm with a fast, simplified potential of mean force (PMF) to evaluate the docking efficiency. The two substrate used in this study are cellobiose and cellotetraose. The active site is confirmed by comparing the docked structure with the available experimental structures. Cellotetraose was found have stronger binding than cellobiose.